Language motivation and attitudes: a study with English for Academic Purposes learners - Cerqueira, Flavia Azeredo; Badger, Shellwyn (Revista Horizontes de Linguistica Aplicada, 2015)
Abstract The study investigates English for Academic Purposes (EAP) course learners’ motivation within the L2 Motivational Self System Framework (cf. DÖRNYEI; CLÉMENT, 2001; DÖRNYEI, 2005; CSIZÉR; DÖRNYEI, 2005b) and their achievement. The framework consists of three components, of which the ideal L2 self is the most important in the maintenance of motivation. Brazilian learners of EAP, students of a federal university in Belo Horizonte, participated in the study. The data was collected by means of questionnaires about attitude and motivation towards the L2, L2 learning and EAP, and also the ethnicity and socioeconomic backgrounds of learners. The EAP course as a program component of a broader, federal Brazilian policy with both national and international stakeholders was also examined. The results suggest that the learners possess a well-established ideal L2 self. The variables measured in this project presented a positive tendency towards L2 motivation. This confirms that the participants were motivated to learn the L2 language, in this case English. The socioeconomic and ethnic variables indicate that whites from a middle-class background are the majority group on campus. Recommendations for further research in L2 motivation and policy studies conclude the paper. Keywords: EAP. Educational policy. International education. L2 motivational self system. Language attitudes. L2 learning. Resumo Este estudo investiga a motivação de aprendizes de Inglês para Fins Acadêmicos (IFA) a partir do Modelo de Autossistema Motivacional na L2 (DÖRNYEI; CLÉMENT, 2001; DÖRNYEI, 2005; CSIZÉR; DÖRNYEI, 2005b) e o aproveitamento dos aprendizes no curso. O modelo de Autossistema Motivacional na L2 consiste de três componentes, nos quais o self ideal na L2é o mais importante para a manutenção da motivação. Os participantes do estudo eram aprendizes brasileiros de IFA, estudantes de uma universidade em Belo Horizonte. Os dados foram coletados em questionários sobre atitude e motivação em relação Ã  L2, aprendizagem de L2 e IFA, bem como informações dos participantes a respeito de questões de etnia e situação socioeconômica. Foi examinado também o curso IFA como componente de um amplo programa de política federal com foco nacional e internacional. Os resultados sugerem que os participantes apresentam um self ideal na L2 bem estabelecido. As demais variáveis indicaram uma tendência positiva em relação Ã  motivação. Esse dado confirma que os participantes estavam motivados para aprender a L2. As variáveis socioeconômicas e étnicas indicaram que os estudantes brancos, de classe média representam o grupo majoritário presente no campus universitário estudado. Palavras-chave: IFA. Políticas educacionais. Educação internacional. Modelo de Autossistema Motivacional na L2. Atitude linguística. Aprendizagem de L2.